2016
DOI: 10.18632/oncotarget.11650
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 controls the EMT switch in murine mammary carcinomain vitroandin vivo

Abstract: We analyzed the molecular basis for carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1)-controlled inhibition of epithelial-mesenchymal transition (EMT) in a mouse model for mammary adenocarcinoma (WAP-T mice). We demonstrate that silencing of CEACAM1 in WAP-T tumor-derived G-2 cells induces epithelial-mesenchymal plasticity (EMP), as evidenced by typical changes of gene expression, morphology and increased invasion. In contrast, reintroduction of CEACAM1 into G-2 cells reversed up-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…The absence of CEACAM1 on hyperplastic tumors correlated with reduced apoptosis of malignant cells 52 . Moreover, CEACAM1 knockout mice lacking CEACAM1 in WAP-T tumor cells had enhanced tumor phenotypes including increased Wnt signaling, promoted cellular invasiveness, and strongly enhanced rate of metastasis of mammary adenocarcinomas in vivo 78 . Miska et al .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of CEACAM1 on hyperplastic tumors correlated with reduced apoptosis of malignant cells 52 . Moreover, CEACAM1 knockout mice lacking CEACAM1 in WAP-T tumor cells had enhanced tumor phenotypes including increased Wnt signaling, promoted cellular invasiveness, and strongly enhanced rate of metastasis of mammary adenocarcinomas in vivo 78 . Miska et al .…”
Section: Discussionmentioning
confidence: 99%
“…Stable expression of CEACAM1 on melanoma cells enhanced invasion and migration of the cells in vitro [9] Reduced expression of CEACAM1 was reported upon malignant transformation in mice [10] and in samples of human colorectal cancer [11]. Similarly, CEACAM1 expression inversely correlated with survival of breast cancer patients [8]. Frequent loss of CEACAM1 in benign and malignant colorectal neoplasias was also reported [7].…”
Section: Introductionmentioning
confidence: 93%
“…Nittka et al found that the Research Paper www.oncotarget.com absence of CEACAM1 on hyperplastic tumors correlated with reduced apoptosis of malignant cells [7]. Moreover, a lack of CEACAM1 in WAP-T tumor cells resulted in increased Wnt signaling, promoted cellular invasiveness, and strongly enhanced the rate of metastasis of mammary adenocarcinomas in vivo [8]. On the other hand, other investigations have suggested a role for CEACAM1 in angiogenesis and suppression of the neoantigen-specific anti-tumor response [3].…”
Section: Introductionmentioning
confidence: 99%
“…Following intra-and extravasation of the vascular system, tumor cells need to have the potential to adapt and survive in the foreign environment of distant organs, where they can then form micro- and finally macro-metastases [75,76]. Significantly, CEACAM1 was also shown to control the epithelial-mesenchymal transition by site-specific regulation of beta-catenin [77]. Therefore, extensive efforts have been made to understand the molecular and cellular mechanisms driving the metastatic cascade with the aim of developing new therapeutic approaches against disseminated cancer cells.…”
Section: Ceacam1 Signaling and Its Function In Melanomamentioning
confidence: 99%